Kushner, Florence (audio interview #2 of 4) - Kushner, Florence ( - 12/1/2002); Paxton, Louise, interviewer
INTERVIEW DESCRIPTION - This is the second of four interviews conducted with Flo Kushner as part of a project for a women's oral history class at CSULB.